Imaging polarimetry and spectropolarimetry of comet C/2013 R1 (Lovejoy). (1st December 2015) - Borisov, Galin; Bagnulo, Stefano; Nikolov, Plamen; Bonev, Tanyu
Abstract: We have obtained imaging polarimetry of the comet C/2013 R1 (Lovejoy) with 2-Channel-Focal-Reducer Rozhen instrument at 2m Ritchey–Chrétien–Coudé telescope of the Bulgarian National Astronomical Observatory Rozhen in two dust continuum filters covering wavelength intervals clear from molecular emissions and centred at 4430 Å in blue filter and at 6840 Å in red filter. In imaging mode we measured the degree of linear polarisation 17.01±0.09% in the blue and 18.81±0.02% in the red, which is in a very good agreement with measurements of other comets at the similar phase angle. We have also obtained polarisation maps in both filters. We found a strong correlation between the spatial distribution of the polarisation and the dust colour. Spectropolarimetry of the nucleus region shows an increase of the polarisation with wavelength, and a depolarisation in the spectral regions with gas emission lines, most noticeable in C2 emission band, which shows a polarisation of 6.0±1.1%. Abstract : Highlights: We have measured the degree of linear polarisation in the blue (4430 Å) and red (6840 Å) continuum filters of the dust ejected from comet C/2013 R1 (Lovejoy), and our results are P 443 = 17.01 ± 0.09 % and P 684 = 18.81 ± 0.02 % . The connection between high polarisation and low reddening in the dust coma was found. The interpretation is that low reddening means small particles, or very dark ones, both of which give high polarisation. Therefore this should be the composition of the observed highly polarised feature. We have obtained a spectropolarimetry of the comet and found the change of the degree of linear polarisation of the dust with wavelength. In the C2 molecule emission band we have measured 6.0±1.1% degree of linear polarisation. We conclude that this lower value of linear polarisation in the C2 molecular band is due to collisions with other species in the comet's coma.